The Optimization Of Cellulose Content In Tobacco Stems (Nicotiana tabaccum L.) With Acid Extraction Method And Alkaline Extraction Method - Andrew Setiawan Rusdianto; Winda Amilia; Vina Julie Dwi Sinta (International Journal on Food, Agriculture and Natural Resources, 2021)
Tobacco stems are the agricultural waste of tobacco crops that have the potential to be utilized. Use of tobacco stems in general, only in the leave of disposal without handling. Tobacco stems have the opportunity as a source of cellulose because they have a relatively high content of cellulose. The use of proper methods also plays an important role in extracting cellulose on tobacco stems. The research aims to determine the efficiency levels of cellulose extract from tobacco stems (Nicotiana tabaccum L.) with acid extraction methods and alkaline extraction. The research used a complete randomized design with a repeated trial of 2 times. The results showed the alkaline method of producing the best results against the rendemen testing parameters, water content, hemicellulose content, cellulose content, lignin content and FTIR spectroscopy. Yield test, moisture content, hemicellulose content, cellulose content and lignin content was at the best in the alkaline extraction with a concentration of 12% the yield of 43.63%; water content of 7.54%; hemicellulose content 14.33%; cellulose content 46.17%; and 2.83% lignin content. FTIR spectroscopy test shows that all treatments have important and specific function groups on cellulose such as – OH, C-H, and-CH2, so that samples were identified of cellulose.